New species of the Genus Messatoporus Cushman (Hymenoptera, Ichneumonidae, Cryptinae) from the Neotropical Region - Lima, Thalita Da Silva; Camargo, Luiza Figueiredo; Dias, Angélica Maria Penteado- (Zootaxa, 2023)
Three new species of Messatoporus are described and illustrated from Brazil: Messatoporus claretee sp. nov., Messatoporus luizae sp. nov. and Messatoporus suzane sp. nov. The species are characterized by having long mandibles, with dorsal tooth much longer than ventral tooth, propodeum with long transverse striation and first metasomal tergite long with spiracle near the middle.